1996
DOI: 10.1111/j.1365-3164.1996.tb00221.x
|View full text |Cite
|
Sign up to set email alerts
|

The cytokine response of afferent lymph following orf virus reinfection of sheep

Abstract: The in vivo dynamics of differentiated cells and interleukin (1L)-1 p, IL-8, granulocyte-macrophage colony-stimulating factor (GM-CSF) and interferon (1FN)q titres in afferent lymph were compared following orf virus reinfection and inactivated virus injection of previously infected sheep. The biphasic lymphoblast and cytokine response in the lymph to virus reinfection is consistent with a response initially to orf virus as recall antigen followed by a response to viral replication. CD4 T cells increased in out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 29 publications
2
42
0
2
Order By: Relevance
“…We did not look for anti-inflammatory granulocyte colony-stimulating factor in our experiments. However, induction of IFN-␣ and -␤, IL-2, and TNF-␣ has been described following a natural infection with PPVO (3,5,6) and could be confirmed in our studies monitoring induction of expression of the mRNA of these cytokines (not shown).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…We did not look for anti-inflammatory granulocyte colony-stimulating factor in our experiments. However, induction of IFN-␣ and -␤, IL-2, and TNF-␣ has been described following a natural infection with PPVO (3,5,6) and could be confirmed in our studies monitoring induction of expression of the mRNA of these cytokines (not shown).…”
Section: Discussionsupporting
confidence: 65%
“…In sheep, the early response is characterized by an influx of neutrophils followed after several days by the accumulation of CD4 ϩ T cells, CD8 ϩ T cells, and B cells adjacent to and underlying PPVO-infected epidermal cells (12)(13)(14)(15). An increase of IL-1, IL-8, and granulocyte-macrophage colony-stimulating factor (GM-CSF) levels followed by rapid decline has been described in natural PPVO infections at very early time points (5). These cytokines are involved in the recruitment of granulocytes to the site of infection as part of the host inflammatory response to this infection.…”
Section: Discussionmentioning
confidence: 99%
“…Lymph samples were from previous experiments (21,23). In these experiments, scabbymouth virus was used to infect Suffolk cross sheep in the hind flank (i.e., the prefemoral lymph node drainage region) by scarification with a needle and topical application of orf virus (10 6 50% tissue culture infective doses [TCID 50 ]).…”
Section: Methodsmentioning
confidence: 99%
“…In these experiments, scabbymouth virus was used to infect Suffolk cross sheep in the hind flank (i.e., the prefemoral lymph node drainage region) by scarification with a needle and topical application of orf virus (10 6 50% tissue culture infective doses [TCID 50 ]). For controls, the virus was inactivated by UV irradiation (21) and the equivalent of ϳ10 6 TCID 50 of virus was injected intradermally into the hind flank. Cannulated pseudo-afferent lymph (herein referred to as afferent lymph) and efferent lymph samples were obtained from reinfected sheep as described previously (21,23).…”
Section: Methodsmentioning
confidence: 99%
“…The virus infects sheep via breaks in the skin around the mouth and causes contagious pustular dermatitis or scabby mouth that spontaneously resolves after 4-6 weeks (McKeever et al, 1988). ORFV has the ability to reinfect its host despite an apparently normal host immune response (reviewed in , albeit these lesions are smaller and resolve faster (10-15 days) (Robinson et al, 1981;McKeever et al, 1988;Haig et al, 1996). Antibody and cell-mediated responses to the virus are induced, although recovery is dependent only on the latter (Buddle & Pulford, 1984;Mercer et al, 1994;Czerny et al, 1997;Lloyd et al, 2000).…”
mentioning
confidence: 99%